f ( x + y 2 n + 1 ) = f ( x ) + f ( y ) 2 n + 1 and n ∈ N
Let f ( x ) be a real function not identically zero satisfying the above condition for any real numbers x , y . And provided with f ′ ( 0 ) ≥ 0 . Then find the value of f ′ ( 1 0 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Hehe yes. I also did the same xD
i too did the same xD!
EXACTLY....lollllll XD😉😉😂😂.!!!!UPVOTED!!!!
Firstly I feel that this does not look like a calculus question at all, but more of a functional equation problem. Just observing f ( x ) is not sufficient to solve this problem, but to prove it.
Disclaimer: The problems states the derivative exists at x = 0 and asks for f ′ ( 1 0 ) . So I assume f is continuous (which I think should be added to the question in some subtle way like f ′ ( x ) ≥ 0 ).
Let y = 0 , then f ( x ) = f ( x ) + f ( 0 ) 2 n + 1 ⟺ f ( 0 ) = 0 . Let x = 0 , f ( y 2 n + 1 ) = f ( y ) 2 n + 1 . Hence substituting that into the original equation and let y 2 n + 1 = z , and note that z covers all reals. Hence we get the Cauchy equation f ( x + z ) = f ( x ) + f ( z ) . Note that this and f ( y 2 n + 1 ) = f ( y ) 2 n + 1 can imply the original equation, so the original equation is equivalent to these two equations. So we know the solution to Cauchy equation is f ( x ) = a x , a ∈ R , since f is not zero, hence a is nonzero. Now for any y , a y 2 n + 1 = f ( y 2 n + 1 ) = f ( y ) 2 n + 1 = ( a y ) 2 n + 1 which forces a = 1 as f ′ ( 0 ) ≥ 0 which is the only application of calculus here. Hence f ′ ( 1 0 ) = 1 .
Note that if we did not use the assumption that f is continuous, I couldn't see how to make more progress.
This probably doesn't work without continuity. It seems reasonable for it to be possible to choose a set of irrationals so that every real number can be written ("uniquely" in some sense) as a finite expression using multiplication, addition, exponentiation with strictly rational powers, the chosen set of irrationals, and rational numbers. Then setting f(x)=1 for each x in the set, and working backwards would result in a well-defined function.
Awesome solution
As it given that f(x) is differentiable .. we can take partial differential wrt x anf clearly sees that f'(x)=constant .. the solution to functional equation is a line... and satisfying conditions f'(x)=1
Problem Loading...
Note Loading...
Set Loading...
JEE style.
We can easily observe that f ( x ) = x satisfies all given conditions.